Analisa Pengaruh Kecerdasan Buatan (AI) Terhadap Kemampuan Berpikir Kritis Mahasiswa - Janter Tampubolon, Rivaldo; Ariesandes, Thoty; Idlal Hafizd, Muhammad; Hidayatullah, Najwan; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
With the increasing use of technology in education, it is essential to understand how Artificial Intelligence (AI) can influence the learning process and the development of critical thinking skills. This study employs regression analysis to evaluate the relationship between AI usage and the critical thinking abilities of students. The research population consists of students from the Faculty of Computer Science, Informatics Engineering Study Program for Working Class in the 5th semester at Universitas Pamulang, with a sample size of 240 respondents selected using stratified random sampling techniques. The results indicate that AI usage has a significant positive impact on critical thinking skills, where students who frequently use AI tend to show improvements in their critical thinking abilities. The integration of AI in learning provides immediate feedback and allows for the adjustment of learning strategies according to individual needs, supporting the development of a more flexible and adaptive mindset. Despite challenges, such as the potential for dependency on technology that may hinder independent thinking skills, this research emphasizes that the utilization of AI in education can be an effective tool for enhancing students' critical thinking abilities. These findings have important implications for educators and educational institutions in designing curricula that wisely integrate AI technology, enabling students to develop into critical and creative individuals in the digital era.